2005
DOI: 10.1379/csc-139r.1
|View full text |Cite
|
Sign up to set email alerts
|

Native folding of aggregation-prone recombinant proteins in Escherichia coli by osmolytes, plasmid- or benzyl alcohol–overexpressed molecular chaperones

Abstract: When massively expressed in bacteria, recombinant proteins often tend to misfold and accumulate as soluble and insoluble nonfunctional aggregates. A general strategy to improve the native folding of recombinant proteins is to increase the cellular concentration of viscous organic compounds, termed osmolytes, or of molecular chaperones that can prevent aggregation and can actively scavenge and convert aggregates into natively refoldable species. In this study, metal affinity purification (immobilized metal ion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
108
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 147 publications
(109 citation statements)
references
References 50 publications
1
108
0
Order By: Relevance
“…These findings are in line with earlier reports that membrane fluidizers, such as benzyl alcohol, cause a HSR at non-inducing temperatures in plants and bacteria. 11,12,28 Thus, in Escherichia coli 19 and Synechocystis 29 preadaptation to different growth temperatures modulated the subsequent heat-induced expression levels of major classes of HSPs and affected thermotolerance.…”
Section: Heat-induced Ca 2+ Influx Is Influenced By the Growth Tempermentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are in line with earlier reports that membrane fluidizers, such as benzyl alcohol, cause a HSR at non-inducing temperatures in plants and bacteria. 11,12,28 Thus, in Escherichia coli 19 and Synechocystis 29 preadaptation to different growth temperatures modulated the subsequent heat-induced expression levels of major classes of HSPs and affected thermotolerance.…”
Section: Heat-induced Ca 2+ Influx Is Influenced By the Growth Tempermentioning
confidence: 99%
“…[8][9][10] Yet, the overexpression of HSPs, so called the heat shock response (HSR), can be activated under mild physiological conditions that are unlikely to cause any protein denaturation in the cell. [11][12][13] Although multiple HSR triggering mechanisms may co-exist, 6,14-16 recent evidences in bacteria, algae, plants and mammalian cells point at the understanding how plants sense and respond to heat stress is central to improve crop tolerance and productivity. recent findings in Physcomitrella patens demonstrated that the controlled passage of calcium ions across the plasma membrane regulates the heat shock response (hSr).…”
mentioning
confidence: 99%
“…This results in enhancement of protein stability (19,20). It has been shown with several proteins that some osmolytes, when added to the growth media, assist protein folding resulting in increased protein solubility (21)(22)(23). Preadaptation of E. coli cells to increasingly high concentrations of salt in the media leads to crosstalk between osmolytes and heat-shock proteins and decreases the tendency of soluble proteins to form insoluble aggregates during heat-shock (24).…”
Section: Introductionmentioning
confidence: 99%
“…Because the raft structure is also dependent on the thermally controlled lipid-phase behavior, we assumed that even mild changes in temperature could result in a fundamentally altered solubility and consequently in the redistribution and activity of potential stress-sensing/signaling proteins in the rafts (4,5). We recently furnished evidence that the drug candidate bimoclomol, its analogs, and the widely used membrane fluidizer benzyl alcohol (BA) are all capable of activating cellular Hsp formation without causing measurable protein denaturation (9)(10)(11)(12)(13).…”
mentioning
confidence: 99%